Implementation of digital performance assessment to measure pharmacy physics laboratory skills - Meiry Akmara Dhina; Ginayanti Hadisoebroto; Sugeng Rifqi Mubaroq; Iyan Gustiana (Momentum: Physics Education Journal, 2021)
This study was motivated by the fact that laboratory skills assessment did not have a specific standard for each assessment. Student performance and skills in doing practicum are not well observed and measured. Meanwhile, the assessment of skills in pharmaceutical physics laboratory learning is considered important. An alternative assess-ment that can measure pharmaceutical physics laboratory skills is to use performance assessment. This research has integrated the work assessment in digital form with the existing web-based electronic module (e-mulsi). Application testing needs to be done to determine the digital performance assessment's effectiveness in assessing the pharmacy physics laboratory's skills. A system test and user test do this. System testing is done by white box testing. Meanwhile, user testing is carried out with an instrument in the form of a questionnaire to laboratory assistants and lecturers as users of the application's per-formance assessment application. The digital performance assessment system's perform-ance test results using GTMetrix ranged from 85% - 62%. This performance assessment application greatly helped the results of the questionnaire for laboratory assistants and lecturers. It greatly facilitated the archiving of each students process in the form of an information technology data base. Lecturers also find it very helpful because the value processing process is easier for applications to do, reducing data processing errors.